How Reliable is the Radiographic Diagnosis of Mild Madelung Deformity? - Farr, Sebastian; Guitton, Thierry G.; Ring, David; Science of Variation Group (Journal of Wrist Surgery, 2018)
Background Patients with Madelung deformity exhibit a spectrum of mild to severe deformity and distortion of wrist geometry. It may be difficult to reliably distinguish mild Madelung deformity from normal.Purpose This study thus tested the reliability of the diagnosis of mild Madelung deformity on a single posteroanterior (PA) radiograph.Materials and Methods An online survey was sent to hand and wrist surgeons of the Science of Variation Study Group for evaluation of 25 PA wrist radiographs comprising five adults with suspected mild Madelung deformity and 20 radiographs without any evident wrist pathology. Interobserver agreement was evaluated both via average percent agreement and Fleiss' kappa. To evaluate the relationship of rater characteristics and accuracy, a linear regression model was computed.Results The interobserver agreement among the 69 participating surgeons was low (Κ = 0.12). The overall sensitivity, specificity, and accuracy were 0.30, 0.86, and 0.75, respectively. The mean confidence was 7.4 ± 0.4 for mild Madelung and 7.8 ± 0.5 for normal (p = 0.112). The observers' confidence level was the only factor which had a mild but significant effect on the accuracy of the ratings.Conclusion The diagnosis of mild Madelung deformity on a single PA radiograph is unreliable.Level of Evidence The level of evidence is II, diagnostic study.
Keywords: Madelung deformity; ulnar tilt; lunate fossa angle; interobserver reliability; wrist pain